Peran Komunikasi Persuasif Orang Tua dalam Membentuk Konsep Diri Positif pada Anak di TK Islam Fatmawati - Maria Ulfah; Asep Gunawan; Falizar Rivani (Pusat riset dan Inovasi Nasional, 2025)
This study presents a description of the role of persuasive communication carried out by parents in shaping a child’s positive self-concept. The research used a qualitative approach with data collection techniques including observation, interviews, and documentation. Purposive sampling was applied to ensure the validity of the data. The findings of the study include: the use of praise and appreciation, time management, utilizing technology as a means of communication, persuasive communication patterns based on Islamic values, and the role of the school environment. The success of parents' persuasive communication lies in the use of gentle and appreciative communication, effective time management despite busy schedules, and the consistent integration of Islamic values both at home and in school.